Things Latinas need to plan for safety: A dual-site concept mapping study - Alisa Velonis; Maria Jose Baeza; Molly McGown; Daisy Magaña; Jasmine Maldonado; Patricia O’Campo; Nicholas Metheny (PLoS ONE, 2025)
Background Latina women in the United States experience intimate partner violence (IPV) at high rates, but evidence suggests Latinas seek help for IPV at lower rates than other communities. Safety planning is an approach that provides those experiencing IPV with concrete actions to increase their safety and referrals to formal services. While safety planning is shown to reduce future incidences of violence, little is known about the safety planning priorities of Latinas. Approach This study leveraged Group Concept Mapping, a mixed-method process consisting of brainstorming, sorting, rating, and interpreting. First, 17 Latinas who were survivors of IPV and/or professional advocates generated responses to a focal prompt. Next, 19 participants pile-sorted a list of unduplicated responses into categories. Data were analyzed using multidimensional scaling and hierarchical cluster analysis and results were iteratively refined by the study team. Forty-two Latina participants in Chicago and Miami rated each item based on its necessity for safety using two scenarios: if a survivor planned to leave a partner or remain in the relationship. Bivariate correlation analyses were used to examine differences in safety planning priorities across multiple axes. Finally, results were shared with participants for feedback and contextualization. Results Combined, a total of 46 Latinas participated in data collection activities. Brainstorming and sorting data generated seven clusters of safety planning needs. Statistically significant differences in cluster rating were found for women who intended to leave a relationship (for whom legal services was most necessary) versus those who intended to stay (for whom safety planning services were critical) and those in Chicago versus those in Miami. Conclusions This study contributes to the small, but growing, literature regarding safety planning needs of Latinas in the US and illustrates potential ways in which future safety planning interventions should be tailored to these communities.